1100. SARS-CoV-2 Seroprevalence in Kenyan Youth living with HIV. (15th December 2022) - Boyle, Mary; Nyandiko, Winstone; DeLong, Allison; Chory, Ashley; Aluoch, Josephine; Ashimosi, Celestine; Munyoro, Dennis; Biegon, Whitney; Gillette, Emma; Lidweye, Janet; Nyagaya, Jack; Sang, Edwin; et al.
Abstract: Background: SARS-CoV-2 seroprevalence studies can inform pandemic spread. By February 2021, estimates demonstrated 11%-62% seroprevalence in diverse Kenyan populations, with geographic variability and temporal increase, and well in excess of 0.2% laboratory-confirmed cases. The impact of HIV on seropositivity, particularly in youth living with HIV (YLWH) is unclear. Methods: During February to September 2021, before SARS-CoV-2 vaccination, we cross-sectionally enrolled perinatally-infected YLWH in western Kenya in four sites (Eldoret, tertiary referral center; urban Kitale, peri-urban Turbo, rural Webuye), and determined seropositivity using the Bio-Rad Platelia assay. Additional evaluations included HIV viral load (VL), CD4 and a COVID-19-focused survey. Multiple logistic regression was used to measure associations of seropositivity with age, gender, enrollment month, site, HIV treatment failure (VL > 1, 000 copies/ml), and CD4 (≥ 500 vs < 500 cells/μL). Results: Of 241 YLWH, 29% were seropositive, 68% seronegative and 4% equivocal. Temporal trends (linear relationship per subsequent enrollment month; Odds Ratio (OR) 1.29 [95% Confidence Interval (CI), 1.06-1.58], p=0.013) and geographic variability (Eldoret-25%, Kitale-20%, Turbo-25%, Webuye-56%; p=0.027) were observed. Presumptive or laboratory-confirmed COVID-19 diagnosis, hospitalization, or death were absent. Self-reported illness was similar among seropositives and seronegatives, and highest in Webuye. Seropositivity was significantly associated with being male (OR, 1.06 [95% CI, 0.57-1.98], p=0.848), and age 15-17 years vs < 15 (OR, 2.57 [95% CI, 1.16-5.93], p=0.023), not with VL or CD4. Among seropositives, above-range titers were seen in 57%. Conclusion: Of 241 Kenyan YLWH, 29% were SARS-CoV-2 seropositive by August 2021, with geographical, temporal, and age differences, and most seropositives mounting a robust response. Increased prevalence in rural Webuye may reflect less widespread mask-wearing, or its location on a busy transit route. Speculations on why seropositivity is low compared to earlier estimations, like HIV status, failed seroconversion, waning immunity, perception of risk promoting adherence to mitigations, or exposure to research-related guidance, should be investigated. Disclosures: Rami Kantor, MD, Gilead Sciences: Grant/Research Support.